Rabies virus in white-nosed coatis (Nasua narica) in Mexico: what do we know so far? - Puebla-Rodríguez, Paola; Almazán-Marín, Cenia; Garcés-Ayala, Fabiola; Rendón-Franco, Emilio; Chávez-López, Susana; Gómez-Sierra, Mauricio; Sandoval-Borja, Albert; Martínez-Solís, David; Escamilla-Ríos, Beatriz; Sauri-González, Isaías; Alonzo-Góngora, Adriana; López-Martínez, Irma; et al. (Frontiers in Veterinary Science, 2023)
Rabies is a neglected disease that affects all mammals, the schedule of preventive medicine campaigns requires the proper identification of variants of the virus circulating in the outbreaks, the species involved, and the interspecific and intraspecific virus movements, to determine the appropriate sanitary measures. Urban rabies has been eradicated in developed countries and is being eradicated in some developing countries. In Europe and North America, oral vaccination programs for wildlife have resulted successful while in Latin America, Asia, and Africa, rabies remains a public health problem due to the wide variety of wild animal species reservoirs. After obtaining recognition from the WHO/PAHO as the first country to eliminate human rabies transmitted by dogs, Mexico faces a new challenge: the control of rabies transmitted by wildlife to humans and domestic animals. In recent years, rabies outbreaks in the white-nosed coati (Nasua narica) have been detected and it is considered that the species has played a significant role in maintaining the wild cycle of rabies in the southeast of Mexico. In this work, we will resume and discuss rabies from white-nosed coatis cases diagnosed at InDRE from 1993 to 2022 and try to figure out the white-nosed coatis' role as an emergent rabies reservoir in the country. A total of 13 samples were registered in the database from the Rabies laboratories of Estado de Mexico (n=1), Jalisco (n=1), Quintana Roo (n=5), Sonora (n=1), and, Yucatan (n=5). Samples from 1993 to 2002 from Estado de Mexico, Jalisco y Sonora were not characterized and we no longer have the samples to carry on. Nine samples were antigenically and genetically characterized. Until now, coatis have not been considered important vectors of rabies virus (RV), our results indicate that surveillance of rabies virus in coatis should be relevant to prevent human cases transmitted by this species.